Kiai Muhaimin and His Outreach Activity of Dakwah for Promoting Moderation and Preventing Conflict: Seeding Pluralism vis-a-vis Preaching Religion - Sobirin, Mohamad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
Dakwah (English: Preaching) by Kiai (English: Javanese terminology referring to a Muslim cleric) commonly takes place in mosques, Islamic Boarding Schools, Majlis Taklim, or other Islamic religious forums. The dakwah is practiced mostly by inviting adherents of Islam to be a truly Muslim (Muslim Kaffah), or evoking non-Muslims to convert their religion into Islam for the sake of their salvation in the hereafter. However, a kiai in Yogyakarta who is familiarly called Kiai Muhaimin has practiced a unique style of dakwah. He preaches Islam not only in his in-group communities and habitual places but also in churches and other religious places of worship. His dakwah thus has been reaching a wide range of places of worship of besides Islamic ones. He did not call for non-Muslims to convert to Islam. Rather, he has promoted tolerance and a better understanding of pluralism. Likewise, he aims his religious standpoints on Islam in Muslim communities for seeding actual pluralism among Muslims. He has formulated a conceptual framework of Islamic moderate dakwah as a philosophical basis for building tolerance and coexistence in Indonesian multicultural society and socio-religious life. Through the organization he established, i.e., FPUB (Interfaith Brotherhood Forum), he put into practice such an Islamic moderation.